2021
DOI: 10.1371/journal.pone.0257149
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria are specifically vulnerable to 420nm light in drosophila which undermines their function and is associated with reduced fly mobility

Abstract: Increased blue light exposure has become a matter of concern as it has a range of detrimental effects, but the mechanisms remain unclear. Mitochondria absorb short wavelength light but have a specific absorbance at 420nm at the lower end of the human visual range. This 420nm absorption is probably due to the presence of porphyrin. We examine the impact of 420nm exposure on drosophila melanogaster mitochondria and its impact on fly mobility. Daily 15 mins exposures for a week significantly reduced mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…albopictus through all developmental stages except for eggs. For example, mitochondria are known to specifically absorb ~ 420-nm light, and this absorption is attributed to the presence of porphyrins 38 . In addition, it has been reported that the absorption of wavelengths of ~ 420 nm by porphyrins interacts with triplet oxygen molecules to form radicals and ROS, leading to cell death [39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…albopictus through all developmental stages except for eggs. For example, mitochondria are known to specifically absorb ~ 420-nm light, and this absorption is attributed to the presence of porphyrins 38 . In addition, it has been reported that the absorption of wavelengths of ~ 420 nm by porphyrins interacts with triplet oxygen molecules to form radicals and ROS, leading to cell death [39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that BL has the potential to damage human eyes contributing to diseases ranging from glaucoma (Ouyang et al, 2020) to retinal degeneration and age-related maculopathy (Algvere et al, 2006); however, little is known about the mechanisms of damage. Recent research on BL effects focused on human retina-related cells in vitro and suggest that BL can increase reactive oxygen species (ROS), cause DNA damage, impair mitochondrial function, and damage lysosomes (Ouyang et al, 2020;Kam et al, 2021). An in vivo model of acute BL phototoxicity was developed in the fruit fly, Drosophila melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…Optical stimulation of mitochondria with specific wavelengths present in natural light modulates their respiration rate, ATP production and impacts on general physiology, a process known as photobiomodulation. 420 nm light is absorbed by mitochondria [ 1 ], specifically the chromophore porphyrin located in the inner mitochondrial membrane. Following 420 nm absorption, porphyrins interact with molecular triplet oxygen to form singlet oxygen, superoxide anion, and hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…670 nm and other longer wavelengths differs in their impact. They are not absorbed by mitochondria directly [ 1 , 3 , 4 ]. Instead, the mechanism of action is proposed to be via light absorption by nanoscopic interfacial water layer surrounding mitochondrial ATP rotor pumps.…”
Section: Introductionmentioning
confidence: 99%